Carbon reduction effect of ESG: empirical evidence from listed manufacturing companies in China - Ye, Jian; Xu, Wenhua (Frontiers in Ecology and Evolution, 2023)
Against the backdrop of global climate change, corporate carbon emissions have increasingly become a focal point, making carbon reduction by companies a pivotal issue. Based on data from Chinese listed manufacturing companies from 2010 to 2020, this paper explores the impact of ESG performance on carbon reduction. The results indicate that ESG performance significantly reduce corporate carbon emissions. Green technology innovation, corporate efficiency, and managerial short-sightedness are vital channels through which ESG promotes corporate carbon reduction. For companies with different environmental regulations, industry competition intensities, and capital intensities, the relationship between ESG performance and carbon reduction varies significantly. Notably, we found that in companies with strict environmental regulations, intense industry competition, and high capital intensity, the carbon-reducing effect of ESG performance is more pronounced. Furthermore, digital transformation positively moderates the relationship between ESG performance and carbon reduction. This study not only provides new empirical evidence for understanding the impact of ESG performance on carbon reduction but also offers valuable insights for businesses and policymakers to promote corporate efforts in carbon reduction and achieve China's "Dual Carbon" goals.